Effects of different specialty protein sources on growth performance of starter pigs - Woodworth, J.C.; Musser, R.E.; Loughmiller, J.A.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred and ten weanling pigs were fed diets containing either soybean meal, spray-dried blood meal, spray-dried red blood cells, select menhaden fish meal, or synthetic amino acids. From d 0 to 7 postweaning, pigs fed either spray-dried whole blood meal or red blood cells had greater ADG and ADFI than pigs fed select menhaden fish meal or added synthetic amino acids. However, from d °to 14 and 0 to 21, no differences in growth performance occurred among pigs fed the various protein sources. However, pigs fed added synthetic amino acids had poorer ADG compared with the mean for pigs fed the other protein sources.
Keywords: Swine; Starter pig performance; Protein source